Should the person be punished? Defeating conclusions from legal conditionals - Gazzo Castañeda, Lupita Estefania; Justus Liebig University Giessen (My University, 2016)
Defeasible reasoning is people s ability to withdraw previously drawn conclusions in light of new evidence. Defeasible reasoning is therefore especially important in law, where exculpatory evidence can bring judges to conclude that an offence should not be punished after all. The aim of this thesis was thus to investigate how people withdraw conclusions from legal rules. In a series of experiments, legal rules were presented as legal conditionals (e.g., If a person kills another human, than the person should be punished for manslaughter ) and embedded in inference tasks together with potentially exculpatory circumstances (e.g., self-defense). Exculpatory circumstances were presented either explicitly as a third premise (Experiments 1, 2, 4, 5), or captured implicitly via preliminary studies (Experiments 6-8). Participants had to decide whether the offender described in the inference task should (Experiments 1, 2, 4-8) or will be punished (Experiments 6-7). In Experiment 3 participants were asked to generate exculpatory evidence. Participants in all experiments were people without legal education (i.e., laypeople), but in Experiments 1-3 lawyers (i.e., advanced law students and graduated lawyers) were also tested. Whereas lawyers defeasible reasoning adhered to the rules of penal code, the results showed that laypeople s defeasible reasoning depended on their own sense of justice. When asked whether an offender should be punished, laypeople ignored potential exculpatory evidence when the offence was highly morally outraging. In these cases, laypeople even had difficulties in retrieving exculpatory evidence from memory. Only when laypeople were asked whether an offender will be punished, were they more willing to also consider exceptions for highly morally outraging offences. Moreover, depending on people s attitudes about offences and offenders, sometimes legally punishable actions were not punished. Two additional experiments (Experiments 9-10) suggested that people are also prone to ignore exceptions for emotionally-charged events in everyday scenarios. The findings are relevant for cognitive psychology because they show the importance of considering domain knowledge and the reasoners personal attitudes and preferences when predicting inferences. Moreover, the results also have implications for law, social psychology, and society: they show how cognitive paradigms can be applied to test socially relevant constructs from legal theory and social psychology.
Keywords: ddc:150